2019
DOI: 10.1038/s41598-019-46462-8
|View full text |Cite
|
Sign up to set email alerts
|

HLA class II-Restricted CD8+ T cells in HIV-1 Virus Controllers

Abstract: A paradigm shifting study demonstrated that induction of MHC class E and II-restricted CD8+ T cells was associated with the clearance of SIV infection in rhesus macaques. Another recent study highlighted the presence of HIV-1-specific class II-restricted CD8+ T cells in HIV-1 patients who naturally control infection (virus controllers; VCs). However, questions regarding class II-restricted CD8+ T cells ontogeny, distribution across different HIV-1 disease states and their role in viral control remain unclear. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 89 publications
(110 reference statements)
0
5
0
Order By: Relevance
“…A question that arises from our results is how TCR specificity impacts on CD4-derived CD8 T cells. Antigen-restricted MHC class II-specific CD8 + T cells have been described in HIVinfected patients (38)(39)(40). Moreover, a recent study reports the in vivo generation of a CD4−CD8ab + MHC II-recognizing lineage from effector CD4 + T cells using murine models of acute infection (41).…”
Section: Discussionmentioning
confidence: 99%
“…A question that arises from our results is how TCR specificity impacts on CD4-derived CD8 T cells. Antigen-restricted MHC class II-specific CD8 + T cells have been described in HIVinfected patients (38)(39)(40). Moreover, a recent study reports the in vivo generation of a CD4−CD8ab + MHC II-recognizing lineage from effector CD4 + T cells using murine models of acute infection (41).…”
Section: Discussionmentioning
confidence: 99%
“…Reports of T cells with αβ TCRs that violate the norms of MHC class restriction date back at least 40 years 15,16 . Class-mismatched T cells or TCRs have since been described in the context of viruses, cancer, autoimmunity, and transplantation [17][18][19][20][21][22][23][24][25][26][27] . Although seemingly rare, they Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the hallmark of MHC class restriction, reports of CD4 + T cells that recognize antigens presented by class I instead of class II MHC proteins, and vice versa, date back nearly 40 years 15,16 . Such "class-mismatched" T cells and TCRs have since been described in the context of viruses, cancer, autoimmunity, and transplantation [17][18][19][20][21][22][23][24][25][26][27] . However, few studies have characterized the molecular properties of mismatched TCRs and the extent to which they follow other paradigms of TCR molecular recognition.…”
mentioning
confidence: 99%
“…It is also not clear if humans can generate unconventional immune responses reported in animal studies. A study of HIV elite controllers showed that HLA-II restricted CD8 + T cell responses exist in humans but are very rare (178), and highly unlikely to be elicited by vaccination. On the other hand, recent studies showed that HLA-E restricted responses are much more common in humans than previously appreciated, which opens up the possibility of inducing such responses by vaccination (179).…”
Section: Cmv-based Vector Vaccinesmentioning
confidence: 99%